Advances in hematology – research that revolutionized patient care - Wach, Małgorzata; Podhorecka, Monika; Cioch, Maria; Hus, Iwona; Wąsik-Szczepanek, Ewa; Sokołowska, Bożena; Hus, Marek (Polish Journal of Public Health, 2015)
In the last decades, substantial strides have been made in the diagnosis, treatment, and prevention of blood diseases. The new drugs to be used in combination with cytostatic therapy have been developed, based on increased understanding of the biology of neoplasia. The diagnosis of several diseases is based exclusively on cytogenetic and molecular analysis which has become a part of routine diagnostic management. Moreover, molecular definition has allowed the introduction of therapy targeted at molecular change characteristic for a given disease. The introduction of novel agents for the treatment of hematological disorders has resulted in a great improvement in response rate and median survival.The aim of this study is to show advances and possible future directions in the treatment of chosen hematological malignancies during the recent decades.